Factors Affecting E-Wallet Adoption Based On Gen Z Perspective In Indonesia: Study In Gopay Application - Jamie Steve Alvaro; Muthya Rahmi Darmansyah (Journal of Management and Business Innovations, 2025)
The increasing of decision to use indicates an increase in promotion, people recommendation and visual content for Gopay e-wallet users. Users of the Gopay application are a benchmark for the success of a company. This study aims to describe the three independent variables selected for the decision to use Gopay in the scope of financial technology where Gopay is one of the popular e-wallets in Medan. The sampling technique used was purposive sampling with a sample size of 100 people. Data analysis was processed using SPSS 25. The results of the study showed that promotion, people recommendation and visual content had a significant effect on the decision to use. This study is expected to provide additional knowledge for companies engaged in Fintech in stimulating people to use e-wallets. In addition, this study provides a basis for business actors to develop strategies in planning and implementing actions in achieving goals of company. Quantitative analysis is the method used in this research. For upcoming researchers might develop this research using qualitative methods and can provide more knowledge and different perspectives in enhancing customer decision behavior.Keywords: Customer Decision Behavior, People Recommendation, Promotion, Visual Content